A COMMUNITY SEMINAR ON INTRODUCING THE EMERGENCY OF COVID-19 IN CHILDREN - Indra Saputra; Silvia Triratna; Desti Handayani; Silmi Kaffah (Fakultas Kedokteran Universitas Sriwijaya, 2021)
The Covid-19 virus infection has spread rapidly worldwide, making it the first pandemic of the 21st century to have caused many deaths (more than 2 million people died). Some shreds of evidence from a range of sources suggest that the rate of Covid-19 cases in children is relatively low, commonly have asymptomatic or mild symptoms, and have low mortality rates. Data released by the Indonesian Pediatrician Association (IDAI) regarding the mortality rate of children infected with Covid-19 is 42% are infants under one year of age. In addition, there are new reports of severe and life-threatening cases of Covid-19 complication in children, which occur 4-6 weeks after infection, known as Multisystem Inflammatory Disease in Children (MIS-C). In order to control the spreading of Covid-19 infection in children, many countries considered temporarily closing the school. However, in September 2021, the Ministry of Education and Culture of Indonesia decided to reopen the school. Schools that provide face-to-face learning for students are schools located in yellow zones or moderate-risk areas. In order to reopen the school safely, the children, teachers, and parents have to obey some strict safety protocols. Even though physically reopening schools might potentially increase the transmission in the community. Due to anticipate the increase in morbidity and mortality, it is very important to increase public knowledge about the signs and symptoms of COVID-19 in children.